Pyramiding of Three Bacterial Blight Resistance Genes in Rice Cultivar Using Marker Assisted Selection - P, Kadu Tanvi; S, Kale Sonam; Narendra R, Chavan; Agrawal, Toshy; Verulkar, S. B. (International Journal of Bio-resource and Stress Management, 2018)
Bacterial leaf blight (BLB) is a major disease of rice, limiting production throughout the world. Xanthomonas oryzae pv.oryzae is highly virulent pathogen, causing major losses in Rice. Present scenario needs development of disease resistant variety through marker assisted selection is the most promising way to improve their performance. Safri-17 is high yielding most popular rice variety of Chhattisgarh but it is highly susceptible to BLB disease. In the present investigation molecular markers were used to introgressed three major BLB resistance genes i.e xa5, xa13 and Xa21 into Safri-17 from a donor line RP-Bio226. Genetic analysis was used to confirm the F2 population for the presence of BLB resistance genes with the help of SSR and STS markers (RM6765, RM13,and pTA248, xa5R/S respectively). Breeding lines with two or three resistance genes were developed and tested for resistance to the BLB. They showed a wider spectrum and a higher level of resistance as compared to lines with only a single gene. The BLB resistance genes in homozygous condition (Xa21Xa21/xa13xa13/xa5xa5) showed resistance disease reaction whereas in heterozygous condition (Xa21xa21/Xa13xa13/Xa5xa5) showed moderate resistance reaction. Similarly two gene combinations gave more resistance reactions as compare to progenies have single gene.